2013
DOI: 10.1266/ggs.88.135
|View full text |Cite
|
Sign up to set email alerts
|

Promoter activity analysis and methylation characterization of LTR elements of PERVs in NIH miniature pig

Abstract: The potential risk of porcine endogenous retrovirus (PERV) transmission is an important issue in xenotransplantation (pig-to-human transplantation). Long terminal repeats (LTRs) in PERV elements show promoter activity that could affect neighboring functional genes. The methylation status and promoter activities of 3 LTR structures (PERV-LTR1, LTR2, and LTR3 elements) belonging to the PERV-A family were examined using luciferase reporter genes in human liver cell lines (HepG2 and Hep3B). The PERV LTR3 element e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…U3 appears to be the most heterogeneous region, with many binding sites for numerous transcription factors ( Scheef et al, 2002 ; Denner et al, 2003 ; Wilson et al, 2003 ; Ha et al, 2007 ; Park et al, 2010 ; Jung et al, 2013b ). In this region, there are direct repeated nucleotide sequences.…”
Section: Perv Molecular Structurementioning
confidence: 99%
See 1 more Smart Citation
“…U3 appears to be the most heterogeneous region, with many binding sites for numerous transcription factors ( Scheef et al, 2002 ; Denner et al, 2003 ; Wilson et al, 2003 ; Ha et al, 2007 ; Park et al, 2010 ; Jung et al, 2013b ). In this region, there are direct repeated nucleotide sequences.…”
Section: Perv Molecular Structurementioning
confidence: 99%
“…The increase in the number of repeats translates into an increase in the transcriptional activity of the retrovirus as well as an increase of the transcriptional activity of the neighboring host genes after the integration of the provirus ( Denner et al, 2003 ). The transcriptional activity of PERVs may also be controlled by DNA methylation and by the inhibition of histone acetylation ( Jung et al, 2008 , 2013b ; Park et al, 2010 ; Ha et al, 2012 ; Matousková et al, 2013 ; Wolf et al, 2013 ).…”
Section: Perv Molecular Structurementioning
confidence: 99%
“…For xenotransplantation, consistent methylation of the U3 region seems important and suggests host suppression of retrovirus expression [103]. In their next studies, the authors analyzed the promoter activity of various PERV LTR elements by the characterization of DNA methylation and their sequences [104,105]. These authors also indicated that the differences in DNA methylation of LTRs seem to be specific for the cell or tissue type [104].…”
Section: The Four Strategies To Prevent Transmission Of Pervsmentioning
confidence: 99%
“…In their next studies, the authors analyzed the promoter activity of various PERV LTR elements by the characterization of DNA methylation and their sequences [104,105]. These authors also indicated that the differences in DNA methylation of LTRs seem to be specific for the cell or tissue type [104]. However, the heavy methylation in the majority of PERV 5’ LTRs was only revealed in porcine tissues.…”
Section: The Four Strategies To Prevent Transmission Of Pervsmentioning
confidence: 99%
“…Jung et al. analyzed the promoter activity and methylation status of long terminal repeat (LTR) elements of porcine endogenous retrovirus (PERV) in NIH miniature pigs. LTR in PERV elements showed promoter activity that could affect neighboring functional genes.…”
Section: Xenozoonosismentioning
confidence: 99%